The semiotics of fortune-telling - Aphek, Edna, 1943- (Foundations of semiotics ;, 1989)
This book presents a semiotic analysis of the linguistic and extralinguistic elements of fortune-telling as part of a larger pragmatic-oriented theory of human communication. The material was collected in Israel, in Hebrew, and parallels are made with other languages and cultures. The analysis is based on dynamic relativism of the multidimensional, transcendental, holistic process of human communication.